Effects of Anemoside B4 on Diarrhea Incidence, Serum Indices, and Fecal Microbial of Suckling Calves - Lu, Meng; Hu, Fengming; Bi, Yanliang; Ma, Tao; Diao, Qiyu; Jiang, Linshu; Tu, Yan (Frontiers in Veterinary Science, 2022)
The study was conducted to evaluate the effects of Anemoside B4 on diarrhea incidence, serum indices and fecal microbial of suckling calves. Sixty newborn Chinese Holstein calves with similar body weight (43.7 ± 3.9 kg) were randomly divided into four groups with 15 calves each, fed the diet which was supplied 0 (CON), 15 (A1), 30 (A2) and 45 (A3) mg / d of Anemoside B4, respectively. The trial period is 56 days. The blood and fecal samples were collected at 28 and 56 days of age. Results show that during the whole trial period, the diarrhea incidence in Group A1, A2, and A3 were significantly lower than that in the Group CON (P < 0.05). Compared with the Group CON, Anemoside B4 supplementation significantly decreased the contents of serum D-lactic acid and diamine oxidase at 28-day-old (P < 0.05). At 56-day-old, the content of serum D-lactic acid in Group A3 tended to be higher (0.05 < P < 0.01), and the content of serum diamine oxidase in Group A3 increased significantly, in comparison with Group CON (P < 0.05). The Group A3 increased the level of Chao1 and Simpson indices at 28-day-old (0.05 < P < 0.01), and Chao1, Observed_species, Shannon, and Simpson indices at 56-day-old (P < 0.05), in comparison to Group CON. Compared with Group CON, 45 mg / d Anemoside B4 supplementation significantly increased the contents of Bacteroidota (at the phylum level), Prevotella (at the genus level) at 28-day-old (P < 0.05), and the content of Sutterella (at the genus level) at 56-day-old (P < 0.05), promoted the processes of energy metabolism, glycan biosynthesis and metabolism, metabolism of cofactors and vitamins (P < 0.05). A positive correlation was observed between Prevotella and metabolism of cofactors and vitamins, energy metabolism, and glycan biosynthesis and metabolism. A positive correlation was observed between Sutterella and energy metabolism. In Conclusion, Anemoside B4 could effectively alleviate calf diarrhea, protect the integrity of intestinal mucosa, and change the structure of intestinal microbiota, indicating the potential value of Anemoside B4 in regulating intestinal microbiota and the prevention of intestinal diseases.